Perlindungan Hukum terhadap Pemutusan Hubungan Kerja (PHK) di Temanggung - Alya Mutiara Dewi; Purwono Sungkowo Raharjo; Rosita Candrakirana (Majelis: Jurnal Hukum Indonesia, 2025)
This research aims to examine the legal protection against employment termination (PHK) in Temanggung and the obstacles encountered in the process of providing such legal protection. The type of legal research used is empirical and descriptive in nature. The approach employed is qualitative. The types of data used in this research include primary data obtained through interviews with respondents, and secondary data in the form of documents, information, books, journal articles, and facts obtained from official documents and legislation. The results of the study show that legal protection against employment termination (PHK) is carried out by the Department of Industry and Manpower of Temanggung Regency through the development of industrial relations and resolution via mediation. The obstacles faced by the Department of Industry and Manpower of Temanggung Regency in providing legal protection against employment termination (PHK) include limited budget for official travel activities, challenges in implementing industrial relations development with companies, the absence of disputing parties, and the lack of knowledge regarding applicable legal provisions.